2010
DOI: 10.1590/s0102-37722010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Crianças e adolescentes institucionalizados: desempenho escolar, satisfação de vida e rede de apoio social

Abstract: RESUMO -Este estudo objetivou investigar as características de jovens institucionalizados e suas famílias. Participaram 155 crianças e adolescentes, de 7 a 16 anos, de instituições da Região Metropolitana de Porto Alegre/RS. A coleta de dados foi realizada por meio de entrevista estruturada, Teste de Desempenho Escolar, Escala de Satisfação de Vida e Mapa dos Cinco Campos. Foi observada a presença precoce de experimentação de drogas, baixo desempenho escolar e alto índice de repetência entre os jovens. As famí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
32

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 18 publications
2
19
0
32
Order By: Relevance
“…For that matter, it is emphasized that one of the functions of every professional that deal with the present issue is to work hard in the sense to preserve the family and community bonds (Negrão & Constantino, 2011;Santos, 2013;Siqueira & Dell'Aglio, 2010).…”
Section: The Care Of Children In Institutional Sheltering Environmentmentioning
confidence: 99%
“…For that matter, it is emphasized that one of the functions of every professional that deal with the present issue is to work hard in the sense to preserve the family and community bonds (Negrão & Constantino, 2011;Santos, 2013;Siqueira & Dell'Aglio, 2010).…”
Section: The Care Of Children In Institutional Sheltering Environmentmentioning
confidence: 99%
“…Nesse contexto, a nova lei e as práticas dos profissionais apontam para o reconhecimento deste lugar especial destinado à família, tanto a natural como a extensa. A família extensa é vista como fonte de apoio a crianças e adolescentes institucionalizados tanto quanto a família nuclear (Siqueira, Tubino, Schwarz & Dell'Aglio, 2009).…”
Section: )" (P3)unclassified
“…In Brazil, few studies investigate the satisfaction of children and adolescents living in institutional care services, but some authors have indicated that it is necessary to constantly reformulate and evaluate shelters due to several structural and procedural flaws found in Brazilian institutions 13,14 to help institutions in the promotion of healthy development.…”
Section: Introductionmentioning
confidence: 99%